PENGARUH STATUS HUBUNGAN BERPACARAN TERHADAP PERILAKU PACARAN BERISIKO PADA MAHASISWA PERANTAU ASAL PAPUA DI KOTA SURABAYA - Christine Ohee; Windhu Purnomo (The Indonesian Journal of Public Health, 2018)
The quality of education in eastern part of Papua is still low so that many teenagers choose to go out the Papua for study.One of the factors of risky sexual behavior among adolescents students is wandered.  The risky dating behavior of Papuan students in Surabaya is 76.7% (Giay, 2017). The purpose of this study is to analyze the impact of dating status with the risky dating behavior among Papuan origin students in Surabaya. This research is an observational analytic research with cross sectional design. The research population was 260 migrant college students from Papua. The research sample was 70 male and female college students. The independent variables of this research were age, sex, relationship status, intention of risky dating behavior, and knowledge level. The statistical analysis were using multiple logistic regression test with the significance level of 5%. The result of this research showed that relationship status influenced college students’ risky dating behavior (p = 0.001), while age, sex, intention of risky dating behavior and knowledge level did not influence college students’ risky dating behavior (p > 0.05). The conclusion of the research is the status of dating relationship has an effect on the risky courtship behavior of Papuan native students in Surabaya city. Therefore, students are advised not to date during the study period.